Pola Pikir Siswa Dalam Memecahkan Soal Geometri Berkaitan Dengan Kemampuan Ruang - Puspitasari, Andini; Putra, Adhitya Pratama; Istiani, Dede; Nuriza, Rafa Dian; Ma’ruf, Abdul Hakim (Universitas Pekalongan, 2025)
This research aims to examine the mindset of students in solving geometry problems from the perspective of spatial ability. This type of research is descriptive qualitative research. The study is conducted to explore and elaborate on the thought processes of students when solving geometry problems in relation to their spatial abilities. The subjects of this research are twelfth-grade students at Perguruan Nasional Senior High School for the 2024/2025 academic year. The research instrument consists of four validated essay questions. Data collection techniques used include tests, interviews, and documentation. The results of the study indicate that subjects with high ability in solving three-dimensional problems have good visualization skills, can formulate problems, and can independently solve complex geometry problems. Students with moderate ability can use diagrams to solve problems, understand basic concepts, and solve questions well, except in the area of pattern recognition. Meanwhile, students with low ability face difficulties in nearly all aspects of testing, particularly in conceptualization, problem-solving, and pattern recognition. Keywords: Geometry problems, mindset, spatial ability